Optimalisasi Pengetahuan Kesehatan Reproduksi Catin Melalui Edukasi Kesehatan - sofia, Sofia Afritasari; Tilawaty Aprina; Indah Kurniasih (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
Reproductive health is key to the continuity of human life from one generation to the next. Good reproductive health conditions in prospective brides and grooms (catin) will have an impact on the quality of future generations. Catin refers to men and women who do not yet have a legitimate bond under both religious and legal terms and are in the process of preparing for marriage. Prospective brides and grooms are the primary target for efforts to improve reproductive health during the preconception period. Therefore, catin need to prepare their reproductive health to ensure they can have quality generations after marriage. To address reproductive health issues in prospective brides and grooms, the Indonesian government has organized premarital courses aimed at preparing a healthy marital life and producing quality offspring. A total of 20 participants attended the premarital course. Premarital counseling is conducted to provide understanding and knowledge about reproductive health, focusing on prospective brides and grooms. Health professionals provide reproductive health education, conduct health checks, and administer TT immunization to the participants. This counseling is essential to ensure that prospective brides and grooms gain sufficient knowledge about reproductive health before marriage.